Activation of Neuregulin 1/ErbB Signaling Is Involved in the Development of TOCP-Induced Delayed Neuropathy - Xu, Hai-Yang; Wang, Pan; Sun, Ying-Jian; Xu, Ming-Yuan; Zhu, Li; Wu, Yi-Jun (Frontiers in Molecular Neuroscience, 2018)
Organophosphate-induced delayed neuropathy (OPIDN) is characterized by progressive axonal degeneration and demyelination of the spinal cord and sciatic nerves. The neuregulin 1/epidermal growth factor receptor (ErbB) signaling pathway is crucial for axonal myelination. In this study, we investigated whether the neuregulin 1/ErbB signaling pathway mediated the progression of OPIDN. Adult hens were given tri-o-cresyl phosphate (TOCP), a typical neuropathic organophosphorus compound, to cause OPIDN. The ErbB inhibitor lapatinib was administered to hens 4 hours prior to and 4 days after TOCP exposure. the neuregulin 1/ErbB signaling pathway was examined for their role in maintaining spinal cord and sciatic nerve fiber integrity. Schwann cell line sNF96.2 was used as the in vitro cell model. The in vivo results showed that TOCP (750 mg/kg body weight, p.o.) induced prominent ataxia and significant axon degeneration in the spinal cord and sciatic nerves. Lapatinib (25 mg/kg body weight, p.o.) treatment attenuated the magnitude of OPIDN clinically and histopathlogically and partially prevented the TOCP-induced activation of neuregulin 1/ErbB signaling pathway. Lapatinib also prevented the TOCP-induced inhibition of neuropathy target esterase (NTE), a key enzyme during the development of OPIDN, and the disturbed metabolism of phosphatidylcholine in sciatic nerves. In addition, lapatinib was shown, in vitro, to protect sNF96.2 cells from TOCP-impaired differentiation through neuregulin 1/ErbB signaling. Our results suggest that neuregulin 1/ErbB, through regulation of NTE activity in the peripheral nervous system, mediates the progression of OPIDN. Thus, this signal may serve as a potential target for the treatment of OPIDN.